L’origine et les ingrédients du discours hagiographique - Van Uytfanghe, Marc (Sacris erudiri, 2011)
Since the Early Imperial period and especially in Late Antiquity, Greek and Latin literature, both pagan and (Judeo-)Christian, produced a number of texts (spiritual biographies, but also other genres) that contain a hagiographical discourse. If one looks for any of the ingredients of this type of discourse exclusively (characters in a specific relation to God or the divine, multiple historical and literary stylization, performative function, virtutes – in the sense of both virtues and miracles – as archetypes), then one can go far back into Classical and Biblical Antiquity. The combination of the ingredients, however, based on what we have and know now, has not really been found before our era. The Life of Mozes by Philo of Alexandria seems to be the first specimen of such a complete hagiographical discourse.